A Scoping Review of Corticosterone-Induced Changes in Ionotropic Glutamate Receptor Levels and Localization in the Rodent Brain: Implications for the Auditory System - Elsa Edlund; Ewa Domarecka; Heidi Olze; Agnieszka Szczepek (Brain Sciences)
Background: The ionotropic glutamate receptor AMPA (AMPAR) mediates fast excitatory synaptic transmission and regulates synaptic strength in various parts of the CNS. Emotional challenges can affect these processes by influencing AMPAR levels and localization via stress hormones, resulting, e.g., in behavioral changes. AMPARs are essential for auditory processing, but their response to stress hormones in the central or peripheral auditory system remains poorly understood. Therefore, this scoping review examines the effects of corticosterone (CORT), a primary stress hormone in rodents, on AMPA receptor levels and localization in the rodent nervous system and considers potential implications for the auditory system. Methods: We systematically searched PubMed, Web of Science, and OVID EMBASE using MeSH terms related to AMPA receptors and corticosterone. Studies were screened based on predefined inclusion criteria, including original research published in English that focused on AMPA receptor subunits (e.g., GluR1-4, GluA1-4, Gria1-4). Of 288 articles screened, 17 met the criteria for final analysis. Results: No reports were found regarding CORT action in the auditory system. Three main experimental models used in the included research were identified: neuronal cultures, isolated tissue cultures, and animal models. Generally, short-term CORT exposure increases AMPAR surface localization and mobility in neuronal cultures, especially in the hippocampus and prefrontal cortex. However, results from animal models were inconsistent due to variations in experimental design and other factors. The isolated tissue study did not provide sufficient data for clear conclusions. Conclusions: Variability in experimental models limits our ability to draw definitive conclusions about the effects of CORT on AMPARs across different regions of the nervous system. The differences in live animal studies highlight the need for standardized methods and reporting. Since AMPARs play a crucial role in auditory processing, CORT-induced changes in neuronal cultures may occur in the auditory system. Further research is needed to explore the specific responses of AMPAR subunits and how stress hormones may influence auditory disorders, which could help identify potential treatment strategies.